Association between Adverse Reactions to the First and Second Doses of COVID-19 Vaccine - Ken Goda; Tsuneaki Kenzaka; Shinsuke Yahata; Masanobu Okayama; Hogara Nishisaki (Vaccines, 2022)
This study investigated the frequency of adverse reactions to COVID-19 vaccines in Japan and the impact of first-dose adverse reactions on second-dose adverse reactions. Individuals who received an mRNA COVID-19 vaccine at our center in March or April 2021 were included. Data were collected using questionnaires. The main factors were age (<40, 40–59, and >60 years), sex, underlying disease, and first-dose adverse reaction. The primary outcomes were incidence of local and systemic adverse reactions (ARs) attributable to the vaccine. Logistic regression was used to calculate odds ratios (ORs) and 95% confidence intervals (CIs). Among 671 participants, 90% experienced local or systemic ARs. An AR to the first dose was associated with a significantly increased risk of an AR to the second dose (OR: 49.63, 95% CI: 21.96–112.16). ARs were less common among men than among women (OR: 0.36, 95% CI: 0.17–0.76). Local ARs were less common among those aged 60 years or older (OR: 0.35, 95% CI: 0.18–0.66), whereas systemic ARs were more common among those aged under 40 years. Information on ARs to the first dose is important for healthcare providers and recipients when making vaccination decisions.